Early stage ecological communities on artificial algae showed no difference in diversity and abundance under ocean acidification - Federica Ragazzola; Matteo Nannini; Giancarlo Raiteri; Andrea Bordone; Regina Kolzenburg; Elisa Romanelli; Gabriella Cerrati; Danilo Pacella; Lori Gabellieri; Fabrizio Andreoli; Gerardo Claps; Claudio Vasapollo; et al. (Hydrobiologia, 2024)

Performance of sorting grids on catching elasmobranchs in a multispecies Mediterranean bottom trawl fishery - Lorenzo Jacopo De Santis; Sara Bonanomi; Elia Bueloni; Andrea Petetta; Olga Annibale; Licia Finotto; Claudio Vasapollo; Carlotta Mazzoldi; Alessandro Lucchetti; Massimiliano Bottaro (Estuarine, Coastal and Shelf Science, 2024)

Effects of the implementation of T90 extension and 52 mm square mesh codend on the bottom trawl hake fishery of the north western Mediterranean - Francesca Ferragut-Perello; Claudio Vasapollo; Maria Valls; Maria Teresa Farriols; Enric Massutí; Beatriz Guijarro; Sergi Joher; Marina Bibiloni-Socias; Francesc Ordines (Frontiers in Marine Science, 2023)
The Spanish bottom trawl fleet operating in the Mediterranean currently uses 40 mm square mesh codends. Its selectivity is still too low to overcome the overall problem of high proportions of immature specimens in the catches. Even for some target species such as the European hake ( Merluccius merluccius ), there are high proportions of individuals smaller than the minimum conservation reference size (MCRS). The aim of the present work is to assess the selectivity of three different configurations of the traditional net (TRA) used in the bottom trawl hake fishery off the northwest Iberian Peninsula, each including the following modifications: i) an extension piece made of 90° turned diamond mesh (T90), ii) a 52 mm square meshed codend (52S), and iii) both modifications combined (EXP). The experimental fishing survey applied two methodologies: alternate hauls to compare the different net configurations; and the covered codend method to calculate the selectivity parameters of 52 mm square meshed codend for the main commercial species. Catch comparisons showed no discard reduction using the T90 extension piece for any of the species analysed, nor any selectivity improvement. Conversely, the 52 mm square meshed codend showed a clear discard reduction for M. merluccius and a generalized improvement of selectivity for most commercial species. This improvement raised the 50% retention length (L 50 ) for M. merluccius to 22.2 cm, well above its MCRS (20 cm), allowing to escape 90% of the undersized individuals. However, the implementation of the 52 mm square meshed codend would involve important economic losses for main target species, like M. merluccius and Mullus barbatus , representing up to 32 and 28% of the incomes, respectively. Considering all analysed species, economic losses using the 52 mm square meshed codend would represent 27% of the incomes obtained using the current 40 mm square meshed codend in force. Despite it, transition analyses showed that the yield per recruit of the main target species would recover after two years, and even increase up to 30% and 17% for M. merluccius and M. barbatus , respectively, after the fourth year of the implementation of the 52 mm square meshed codend.

Testing experimental devices in the extension piece to increase the selectivity of bottom trawl in the Nw Mediterranean - Mario Sbrana; Francesco De Carlo; Alessandro Ligas; Andrea Massaro; Claudia Musumeci; Ilaria Rossetti; Marina Sartini; Claudio Vasapollo; Claudio Viva; Paolo Sartor; Carlo Pretti (Frontiers in Marine Science, 2022)
In the Mediterranean, experiments and technical measures aimed at improving the selectivity of bottom trawl nets mostly concern modifications to the codend. Grids have been tested in various areas, but have not been adopted for management purposes so far. The present study aims to evaluate whether the adoption of diamond meshes turned by 90° (T90 configuration) and a selection grid with 2 cm bar spacing, both placed in the extension piece of a commercial bottom trawl net, can contribute in reducing the capture of specimens under the Minimum Conservation Reference Size (MCRS) for the main commercial species. The results indicated that the T90 configuration has no effect compared to the commercial net commonly used by fishers. The grid showed a reduction of the catches of European hake individuals between 11 and 19 cm Total Length (TL). However, the use of this device reduced the catch of many species, such as red mullet, deep-water rose shrimp and broad tail short fin squid. This reduction was observed also for specimens above MCRS. In conclusion, the T90 applied to the extension piece does not provide any improvement in selectivity, contrary to what has been observed when the T90 is placed at the codend. In contrast, the grid could be a possible way to increase selectivity. However, the use of grid should be further investigated to identify settings that can avoid the loss of a substantial fraction of commercial catch.

An overview of bottom trawl selectivity in the Mediterranean Sea - ALESSANDRO LUCCHETTI; MASSIMO VIRGILI; CLAUDIO VASAPOLLO; ANDREA PETETTA; GIADA BARGIONE; DANIEL LI VELI; JURE BRĈIC; ANTONELLO SALA (Mediterranean Marine Science, 2021)
In the Mediterranean Sea, where bottom trawling for demersal species is the most important fishery in terms of landings, around 75% of the assessed fish stocks are overfished. Its status as one of the world’s most heavily exploited seas and the one subject to the highest trawling pressure has become a global concern. An extensive review of bottom trawl selectivity studies was performed to assess the sustainability of this fishery in the Mediterranean; the selectivity parameters were collected from 93 peer-reviewed publications of 10 countries, totalling 742 records and 65 species. The review highlighted that i) the catch of bottom trawls commonly employed in the Mediterranean, even complying with current regulations on codend meshes, still includes immature individuals for 64-68% of the species investigated, and individuals under the minimum conservation reference size (MCRS) for 78% of the species investigated, and that ii) the MCRS set for 59% of the species analyzed is well below their length at first maturity, and is therefore ecologically inadequate. Although square-mesh codends are slightly more selective, the models developed herein demonstrate that improving size and species selectivity would require considerably larger meshes, which may significantly reduce profitability. The urgent need to reduce the biological impacts of bottom trawling in the Mediterranean should be addressed by promoting the adoption of more ecologically sustainable fishing gears through the introduction of more selective meshes or gear modifications.

Age and Growth of Striped Venus Clam Chamelea gallina (Linnaeus, 1758) in the Mid-Western Adriatic Sea: A Comparison of Three Laboratory Techniques - Giada Bargione; Claudio Vasapollo; Fortunata Donato; Massimo Virgili; Andrea Petetta; Alessandro Lucchetti (Frontiers in Marine Science, 2020)

Estimating selectivity of experimental diamond (T0) and turned mesh (T90) codends in multi-species Mediterranean bottom trawl - ANDREA PETETTA; BENT HERRMANN; MASSIMO VIRGILI; ROCCO De MARCO; GIOVANNI CANDUCI; DANIEL Li VELI; GIADA BARGIONE; CLAUDIO VASAPOLLO; ALESSANDRO LUCCHETTI (Mediterranean Marine Science, 2020)
The effect of shifting from a diamond mesh codend (T0) to a 90° turned mesh codend (T90) on the size selectivity of seven commercially important species in the Mediterranean bottom trawl fishery was evaluated. During sea trials conducted in the north-western Adriatic, two experimental codends made of 54 mm nominal mesh size netting that differed only in mesh configuration were alternately mounted on the same trawl. Overall, the size selectivity was significantly improved for all the species analysed, shifting from T0 to T90. The difference in the average expected L50values between T90 and T0 was particularly marked in European hake (Merluccius merluccius, 21.26 vs 11.26 cm total length), common squid (Loligo vulgaris, 12.06 vs 7.88 cm mantle length) and mantis shrimp (Squilla mantis, 20.78 vs 13.35 mm carapace length). Both codends had an excessive size selectivity especially for red mullet (Mullus barbatus), Mediterranean horse mackerel (Trachurus mediterraneus) and whiting (Merlangius merlangus), thus involving a commercial loss. These findings demonstrate the efficiency of the T90 codend tested at excluding undersized specimens, especially of hake, whose average L50was above the minimum conservation reference size of 20 cm. The adoption of this practical and inexpensive solution could help improve the management of the demersal resources targeted by the Mediterranean bottom trawl fishery.

Impact on Macro-Benthic Communities of Hydraulic Dredging for Razor Clam Ensis minor in the Tyrrhenian Sea - Claudio Vasapollo; Massimo Virgili; Giada Bargione; Andrea Petetta; Rocco De Marco; Elisa Punzo; Alessandro Lucchetti (Frontiers in Marine Science, 2020)

Reducing Sea Turtle Bycatch in the Mediterranean Mixed Demersal Fisheries - Alessandro Lucchetti; Giada Bargione; Andrea Petetta; Claudio Vasapollo; Massimo Virgili (Frontiers in Marine Science, 2019)

Intertidal Mediterranean Coralline Algae Habitat Is Expecting a Shift Toward a Reduced Growth and a Simplified Associated Fauna Under Climate Change - Agnese Marchini; Federica Ragazzola; Claudio Vasapollo; Alberto Castelli; Gabriella Cerrati; Federica Gazzola; Chulin Jiang; Joachim Langeneck; Maria Chiara Manauzzi; Luigi Musco; Matteo Nannini; Jurgita Zekonyte; et al. (Frontiers in Marine Science, 2019)

Skeletal alterations and polymorphism in a Mediterranean bryozoan at natural CO2 vents - Chiara Lombardi; Maria Cristina Gambi; Claudio Vasapollo; Paul Taylor; Silvia Cocito (Zoomorphology, 2011)